High serum 8-hydroxy-2′-deoxyguanosine levels predict DNA damage and aging in professional divers - Gunes,Ali Erdal (2021)
SUMMARY OBJECTIVE: Reactive oxygen species and oxygen free radicals cause oxidative damage to lipids, proteins, and cell DNA in the cell membrane. Although many DNA products are produced during oxidative DNA damage, 8-hydroxy-2′-deoxyguanosine (8-OHdG) is the most common one, since it can be produced in in vivo environment. In recent years, diving has been done quite frequently for business and sports purposes all over the world. Increased environmental pressure in diving leads to hyperoxia and causes oxidative stress. METHODS: The acute effects of diving on DNA damage were evaluated by comparing 8-hydroxy-2′-deoxyguanosine values of 15 professional diver groups before and after diving. In addition to the demographic characteristics, the serum 8-hydroxy-2′-deoxyguanosine levels of these 15 divers were compared with the control group consisting of nondiving medical students to examine the chronic effect of diving on DNA damage. RESULTS: After deep dive, the amount of 8-hydroxy-2′-deoxyguanosine increased significantly in the diver group and acute DNA damage was observed (T1: 38.86±4.7; T2: 51.77±4.53; p<0.05). In the control group, the amount of 8-hydroxy-2′-deoxyguanosine was insignificant (C1: 47.48±3.73; T1: 38.86±4.7; p>0.05). CONCLUSIONS: It was found that air dives caused an increase in serum 8-hydroxy-2′-deoxyguanosine levels, leading to acute oxidative stress and aging. However, there is no chronic side effect, according to the study of samples taken from the control group. This was thought to be due to the relative sedentary life of the control group. The duration of the effect or the ability to return to normal values should be investigated with further studies planned with large populations.